Pengaruh Brand Ambasssador dan Fanatisme Terhadap Loyalitas Pelanggan Tokopedia dalam Perspektif Ekonomi Islam - Khairawati, Salihah (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2023)
The purpose of this study is to determine the direct effect of brand ambassadors and fanaticism on customer loyalty and find out how according to an Islamic economic perspective on fanaticism. This research method uses quantitative research with an associative approach. The sample technique used is non-probability sampling with purposive sampling with the criteria consisting of members of the ARMY INDONESIA telegram group, BTS fans, aged 12-24 years, and have made at least one purchase transaction on Tokopedia. The data processing technique uses the IBM SPSS 25 Statistical application. The results show that 1) brand ambassador has no effect on customer loyalty as evidenced by tcount 1.313 < ttable 1.984. 2) fanaticism has an effect on customer loyalty as evidenced by tcount 2.885 > ttable 1.984. 3) brand ambassador and fanaticism have an effect on customer loyalty as evidenced by fcount 12.985 < ftable 3.09. 4) fanaticism in the perspective of Islamic economics that in idolizing someone should not be excessive and must be in accordance with the teachings of Islamic law.